Konflik Kepentingan Dalam Putusan Mahkamah Konstitusi Nomor 90/PUU-XXI/2023: Adopsi Ketentuan Judicial Disqualification Negara Amerika dan Kanada - Komarra, M. Akbar Arri; Ridlwan, Zulkarnain; Muhtadi, Muhtadi (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
Decision Number 90/PUU-XXI/2023 is very problematic how the Constitutional Court Judges in their authority actually handle cases that should be returned by the lawmaking body (open legal policy) and have made new norms. The inconsistency of interpretation into the realm of open legal policy and the doctrine of the Constitutional Court as a negative legislator is also evident in Constitutional Court Decision Number 29-51-55/PUU/XXI/2023, which needs to be analyzed from the independence and impartiality of the judiciary. This research method refers to normative research conducted by conducting a study of the principles and applicable laws and regulations relating to the legal issues to be discussed. The research was accompanied by literature studies in the form of books, journals, and decisions as reference materials for research. Data analysis uses descriptive analytics to describe legal phenomena that occur in society through analysis obtained through deductive data to be concluded specifically. The results showed that the conflict of interest that accompanied the Constitutional Court Decision Number 90/PUU-XXI/2023 reduced the quality of the Constitutional Court's independence and the impartiality of its judges. The legal events that the author found in such a way contradict the initial spirit of the establishment of the Constitutional Court. The independence of the Constitutional Court institutionally is considered to have exceeded the limits of authority by handling the case of the age limit of the presidential and vice presidential candidates, which should be owned by the lawmaking body, as well as the inconsistency of previous decisions that create new norms without any clear disadvantages. Conflict of interest was also present in the judicial process, where the composition of the judges changed instantly when Anwar Usman attended the RPH, which was originally the majority of judges refused to partially grant.